Pemanfaatan Media Animasi Dalam Meningkatkan Hasil Belajar IPA Pada Peserta Didik Kelas VIII A di SMP Negeri 4 Sindue - Karninsy, Lastri; Non Shamdas, Gamar Binti; Alibasyah, Lestari; Lilies, Lilies; Febriani, Vita Indri; Buntu, Amalia (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to improve students' learning outcomes by utilizing discovery learning-based animated video media using a scientific learning approach in science subjects of class VIII A at SMP Negeri 4 Sindue. The sample in this study were VIII A class students totaling 15 people. This type of research is classroom action research (PTK), data analysis techniques are qualitative and quantitative analysis. Based on the results of research on the utilization of animation media, it shows an increase in student learning outcomes to reach the predetermined completeness of 75%. The percentage of students' classical learning completeness in cycle I only reached 6.7% while in cycle II it reached 82.67%, this shows a significant increase. The percentage of teacher activity in the application of this learning method reached 88.23% in cycle I while in cycle II it reached 93.39% with a very good predicate. In addition, the percentage of student activity in cycle I reached 88.23% and in cycle II reached 93.39% with a very good predicate. This increase in student activity contributed significantly to the increase in learning outcomes, because students became more active, interested and understood the material well. This research implies that animation media can be used as an innovative alternative for teachers to increase student involvement and learning outcomes in science learning.